Susceptibility of Dog, Hamster, and Mouse Cells to the Replication-Competent Adenovirus 11p E1/E3 Green Fluorescence Protein Vector Has Implications for the Selection of Animal Vaccine Models - Gokumakulapalle, Madhuri; Wang, Li; Mei, Ya-Fang (Frontiers in Microbiology, 2021)
Human adenovirus (Ad)-vectored vaccines require viruses that can internalize into host cells and express the vaccine antigen. Evaluation of the expressed antigen in animal cells is a critical step in preclinical trials of viral vaccines. Due to the species specificity of Ads, it is difficult to find a suitable animal model. Thus, in this study, we compared the efficacy of Ad 11 prototype (Ad11p)-mediated green fluorescence protein (GFP) expression in cell lines of dog (MDCK), hamster (CHO), and mouse (McCoy and C127). Although these cell lines did not express the known primary cellular receptors for Ad11p virus infection (i.e., CD46), Ad11pE1GFP could infect and express GFP with various efficacies. For instance, it manifested relatively higher GFP expression in MDCK than in CHO, McCoy, and C127. However, infection leading to efficient viral release was not observed in any of the studied cell lines. The apparent differences were attributed to particularities of mouse and hamster cell lines, which might have led to the repression of viral DNA synthesis and to the low level of GFP expression mediated by Ad11pe3GFP. Moreover, our results revealed that undetectable hexon protein hampered the assembly of virus particles in CHO and MDCK cells. Ad11p differed from Ad5 in the ability for viral DNA synthesis when infecting CHO cells. Although a defective Ad has been successfully developed for SARS-CoV-2 vaccines in clinical applications, it has been difficult to generate one that can be used as an oral SARS-CoV-2 vaccine. Fortunately, our replication-competent Ad 11p vector might solve this problem. Regarding the use of Ad-vector candidates for vaccine purposes, this study demonstrates the selection of animal cell lines and determination of suitable virus doses in in vitro experiments.